The influence of age of learning on syllable structure in the L2 speaker. - Boron, Anna M. (University of Ottawa (Canada), 1999)
Age of Arrival (AOA) in the L2 community has been a factor in several L2 acquisition studies examining various phonological phenomena, such as consonant perception and vowel perception and production (e.g. Flege et al., 1995; Flege et al., 1997). The literature on phonological acquisition in L2 is not informative, however, on the question of syllable structure. This study addresses the issue of the degree to which syllable structure is subject to modification as a function of AOA. Subjects in the study were mature Italian speakers, whose L2 (English) phonology has presumably plateaued. They were divided into two groups based on their AOA in Canada (Early NI [arrival in Canada between the ages of 2 and 13] and Late NI [arrival in Canada between the ages of 15 and 26]). Italian differs from English in a number of ways. The legality constraints, such as permissible consonant phonemes and their combinations in coda position differ for the two languages. These constraints were examined in this study along-side the effect of stress. Stress, a language-particular constraint, was expected to affect syllabification of Native English (NE) speakers. Legality and stress were explored in a "word game", where subjects were asked to resyllabify bisyllabic nonsense words. (Abstract shortened by UMI.)
Keywords: Language, Linguistics.